2015
DOI: 10.1016/j.sjdr.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Infant oral health care knowledge and awareness among parents in Abha city of Aseer Region, Saudi Arabia

Abstract: Kids under the age of 5 years generally spend most of their time with their parents. It has been found that young children's oral health maintenance and outcomes are influenced by their parent's knowledge and beliefs. This study was done to assess the parent's knowledge about the oral health of their kids aged 1-5 years. The study bases it findings on the survey conducted at the Diagnosis Clinic of the King Khalid University, Abha through a 20-items questionnaire, which was distributed to 425 parents by the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 10 publications
2
35
1
6
Order By: Relevance
“…On the other hand, considering the varieties of space maintainers, the children's reactions and their comfort and satisfaction with treatments involving space maintainers might be different, and the lack of child satisfaction might result in attempts to destroy, break or remove the space maintainer [3]. The dentist will be able to offer the best treatment plan according to his/her knowledge about the children' acceptance rate of different types of space maintainers so that the arch length can be maintained and a proper occlusal relationship can be achieved for the patient through the long-term use of the space maintainer with stable aesthetic results and a functional occlusion [4]. Nagarajappa et al [5] reported that the actual disease and the perceived needs for treatment are significantly correlated with the parent's perceptions and awareness of their children's oral health.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, considering the varieties of space maintainers, the children's reactions and their comfort and satisfaction with treatments involving space maintainers might be different, and the lack of child satisfaction might result in attempts to destroy, break or remove the space maintainer [3]. The dentist will be able to offer the best treatment plan according to his/her knowledge about the children' acceptance rate of different types of space maintainers so that the arch length can be maintained and a proper occlusal relationship can be achieved for the patient through the long-term use of the space maintainer with stable aesthetic results and a functional occlusion [4]. Nagarajappa et al [5] reported that the actual disease and the perceived needs for treatment are significantly correlated with the parent's perceptions and awareness of their children's oral health.…”
Section: Introductionmentioning
confidence: 99%
“…Sehingga dapat disimpulkan bahwa baim orang tua yang bekerja maupun orang tua yang di rumah dalam penelitian yang telah dilakukan memiliki perspektif yang cukup baik terhadap kesehatan gigi anak dilihat melalui data yang didapat meliputi kesadaran orang tua dalam mengajarkan anak menggosok gigi, upaya-upaya yang dilakukan orang tua dalam menjaga kesehatan gigi anak, membiasakan anak menggosok gigi sejak usia 1-2 tahun. Hal tersebut sesuai dengan rekomendasi American Academy of Pediatric Dentistry (AAPD) bahwa bayi harus berkonsultasi dengan dokter gigi dalam waktu 6 bulan untuk mendapatkan gigi pertama mereka atau pada ulang tahun pertama mereka (Alshehri, 2015). Akan tetapi orang tua belum cukup baik dalam memahami karies gigi pada anak.…”
Section: Hasil Penelitianunclassified
“…Peningkatan pengetahuan orang tua mengenai kesehatan mulut melalui intervensi seperti wawancara motivasi dan bimbingan antisipatif memiliki potensi untuk meningkatkan kesehatan mulut anak melalui perubahan perilaku (Manton, 2018). Untuk menentukan langkah yang dapat diambil dalam upaya meningkatkan perspektif dan kepedulian orang tua terhadap kesehatan gigi anak, hal yang perlu dilakukan antara lain mengidentifikasi peran yang sangat diperlukan orang tua tentang perawatan kesehatan untuk anak-anak mereka, menilai pengetahuan dan sikap orang tua tentang kesehatan mulut bayi, memberi edukasi kepada orang tua tentang kebersihan mulut adalah langkah penting selanjutnya karena orang tua adalah pemberi perawatan primer (Alshehri, 2015). Edukasi untuk orang tua mengenai pentingnya menjaga kesheatan gigi dan mulut anak dapat dilakukan oleh layanan pendidikan anak usia dini dengan cara mengadakan sosialisasi kesehatan anak.…”
Section: Pembahasanunclassified
“…Compiling the results obtained from the present study it can be easily shown that the parental knowledge about sealants is low, which in turn signifies the low level of sealant awareness among the general public. The low level of sealant knowledge in the general public maybe due to the lower level of dental awareness and education among the people or the lesser frequency of dental visits [25][26][27]. This irregular dental visits may also cause a scenario whereas the clinician cannot explain or promote the aspects of prevention of caries.…”
Section: Group3-teachers Of the Participant Childrenmentioning
confidence: 99%